New Hydrangeas for North and Central Florida: Bigleaf and Mountain Hydrangeas - Gary W. Knox (EDIS, 2012)
Discoveries of reflowering hydrangeas have resulted in the introduction of many new cultivars, providing more garden impact and strengthening ongoing hydrangea appreciation. Even prior to the new reflowering cultivars, gardeners and landscapers had renewed interest in hydrangeas because they flower in shade, often produce blue flowers, and are considered an “heirloom” plant that reminds us of the garden heritage of our forefathers. Many of the newer cultivars have superior form and disease resistance, and some provide 15 or more weeks of flowering per year in north Florida. This revised 5-page fact sheet was written by Gary W. Knox and published by the UF Department of Environmental Horticulture, September 2012.